2021
DOI: 10.3390/ijerph18083885
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Immediate Electronic-Based Feedback to Enhance Feedback for First-Time CPR Trainees

Abstract: Sudden cardiac arrest is one of the leading causes of death globally. The recommended clinical management in out-of-hospital cardiac arrest cases is the immediate initiation of high-quality cardiopulmonary resuscitation (CPR). Training mannequins should be combined with technology that provides students with detailed immediate feedback on the quality of CPR performance. This study aimed to verify the impacts of the type of feedback (basic or detailed) the responders receive from the device while learning CPR a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Although the general public is not expected to administer drugs or engage in advanced life support (ALS), a deeper understanding of the broader implications of timely bystander CPR can highlight its critical role in the entire emergency response process. A comprehensive training program that offers insights into the significance of early intervention and its potential downstream effects, without delving into the specifics of drug choices, could foster a more informed and proactive approach to bystander interventions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the general public is not expected to administer drugs or engage in advanced life support (ALS), a deeper understanding of the broader implications of timely bystander CPR can highlight its critical role in the entire emergency response process. A comprehensive training program that offers insights into the significance of early intervention and its potential downstream effects, without delving into the specifics of drug choices, could foster a more informed and proactive approach to bystander interventions [30].…”
Section: Discussionmentioning
confidence: 99%
“…CPR training using real-time device feedback for nurses and nursing students showed that the accuracy of chest compressions, mouth-to-mouth ventilation, and overall performance ability improved when compared pre-and postdevice feedback and this was statistically significant when compared to a control group of students who received CPR training without the device [32][33][34]. Trainees subjectively prefer the feedback given by devices, noting less bias compared to instructor feedback and stating an increase in motivation to learn and improve the quality of their CPR [28,35]. In medical student training of CPR skills, supplementing visual feedback devices during simulated cardiac arrest resuscitations resulted in an increased ratio of full chest recoil, while maintaining adequate chest compression depth and rate [36][37][38].…”
Section: Real-time Feedback Devicesmentioning
confidence: 98%
“…CPR feedback devices are widely utilized in CPR training. In studies investigating CPR training, it has been observed that training with a feedback device enhances CPR competency and overall quality more significantly than traditional CPR training methods [35]. Furthermore, the utilization of feedback devices can augment skill acquisition and overall performance in cardiopulmonary resuscitation [36].…”
Section: Application Status and Effects Of Cardiopulmonary Resuscitat...mentioning
confidence: 99%